Method for preparing foil

By adhering the release film to the copper foil prepared by electrolytic method and peeling it off, the problem of tearing the edges of the copper foil is solved, and the preparation and quality improvement of the thinner copper foil is achieved.

CN119890322APending Publication Date: 2025-04-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311395742.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

In secondary batteries, when the copper foil prepared by electrolysis is too thin, it is prone to cause edge tearing problems, making it difficult to prepare copper foil with thinner thickness.

Method used

Adhesive release film to the raw foil and peels it from the roller body with the raw foil, and then removes the release film to improve the edge tearing problem of the copper foil.

Benefits of technology

By adhering the release film to the raw foil, the stability of the raw foil is improved, the edge tearing problem is effectively improved when peeling from the roller body, the preparation of thin or even ultra-thin copper foil is realized, and the width and quality of the raw foil is increased.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890322A_ABST
    Figure CN119890322A_ABST
Patent Text Reader

Abstract

According to the method for preparing the foil, the release film is adhered to the raw foil, so that the stability of the raw foil can be improved, and when the raw foil is stripped from the roller body, the edge tearing problem of the raw foil can be effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a method for preparing a foil material. Background Art

[0002] In secondary batteries, the current collector is the collection carrier for electron energy transfer. Copper foil is usually used as the negative electrode current collector. As the performance requirements of secondary batteries increase, the thickness of copper foil is getting thinner and thinner. However, when copper foil is prepared by electrolysis, it is difficult to peel off the cathode roller if the copper foil is too thin, and it is easy to tear the edge, which makes it difficult to prepare thinner copper foil.

[0003] Therefore, how to improve the edge tearing problem of copper foil has become an important research topic. Summary of the invention

[0004] In view of the problems existing in the background technology, the present application provides a method for preparing a foil material, which can effectively improve the edge tearing problem when the foil material is peeled off from a roller body.

[0005] The method for preparing a foil provided in the first aspect of the present application comprises the following steps:

[0006] The green foil is formed on the roll body by electrolysis;

[0007] Adhering a release film to the raw foil;

[0008] Peeling the raw foil and the release film off the roller;

[0009] Remove the release film.

[0010] The present application can improve the stability of the raw foil by adhering a release film to the raw foil, so that when the raw foil is peeled off from the roller, the tearing problem of the raw foil can be effectively improved. The release film can be removed from the raw foil later without affecting the performance of the raw foil. The method can realize the preparation of thinner raw foil, especially ultra-thin raw foil, and compared with the existing preparation method, the width of the raw foil can be increased, thereby improving the quality and use effect of the raw foil.

[0011] In some embodiments, according to the first aspect, a first example of the first aspect is provided, before removing the release film, the peel strength between the release film and the raw foil is 1N / 25mm or more, preferably 1-5N / 25mm. During the process of removing the release film, the peel strength between the release film and the raw foil is 0.3N / 25mm or less.

[0012] The release film used in the present application can be removed after being processed under certain conditions. By optimizing the peeling strength between the release film and the raw foil within the above range, the present application can not only peel the raw foil and the release film from the roller body together, thus improving the tearing problem of the raw foil, but also remove the release film from the surface of the raw foil after peeling, thus reducing the residual release film.

[0013] In some embodiments, according to the first aspect, a second example of the first aspect is provided, wherein the release film includes a UV anti-adhesion film.

[0014] By optimizing the type of release film, it is convenient and quick to remove it after the peeling step, which can reduce damage to the raw foil.

[0015] In some embodiments, according to the first aspect, a third example of the first aspect is proposed, and removing the release film includes: changing at least one of the following conditions: light energy, light wavelength, and illumination time, so that the peeling strength between the release film and the raw foil is reduced to below 0.3N / 25mm, thereby removing the release film.

[0016] The release film of the present application is easy to remove, has a simple process, is convenient to operate, and is suitable for large-scale industrial production.

[0017] In some embodiments, according to the first aspect, a fourth example of the first aspect is provided, and the release film covers the entire surface of the raw foil.

[0018] Adhering the release film to the entire surface of the raw foil is conducive to completely peeling off the raw foil and improving the problems of edge tearing and tape breakage. A raw foil roll with a length of more than 10,000 meters can be obtained without the risk of tape tearing or tape breakage in the middle of the process.

[0019] In some embodiments, according to the first aspect, a fifth example of the first aspect is provided, and the thickness of the raw foil is 1-2 μm.

[0020] The thinner the raw foil is, the more likely it is to have edge tearing and tape breakage problems. However, the method of the present application can be used to prepare ultra-thin raw foil with a thickness of 1-2 μm, which is not prone to edge tearing and tape breakage problems, thus overcoming the difficulty in preparing ultra-thin raw foil.

[0021] In some embodiments, according to the first aspect, a sixth example of the first aspect is provided, after the peeling and before the removal of the release film, further comprising: forming a transition metal layer on the surface of the raw foil.

[0022] By forming a transition metal layer on the surface of the raw foil, an alloy foil can be obtained, which can not only improve the strength of the raw foil, such as tensile strength, thereby improving the mechanical properties of the raw foil; it can also cover some small defects on the raw foil (such as pinholes and small holes) to improve the quality of the raw foil; it can also improve the thickness and corrosion resistance of the raw foil.

[0023] In some embodiments, according to the first aspect, a seventh example of the first aspect is provided, wherein the material of the transition metal layer includes one or more of nickel and molybdenum.

[0024] By optimizing the material of the transition metal layer, it is helpful to improve the strength of the raw foil and obtain high-quality raw foil.

[0025] In some embodiments, according to the first aspect, an eighth example of the first aspect is provided, wherein the thickness of the transition metal layer is 20-100 nm.

[0026] Controlling the thickness of the transition metal layer within the above range is beneficial to enhancing the mechanical properties of the alloy foil.

[0027] In some embodiments, according to the first aspect, a ninth example of the first aspect is provided, wherein the transition metal layer is formed by sputtering. Optionally, the sputtering method includes one or more of magnetron sputtering, direct current sputtering, and radio frequency sputtering.

[0028] Compared with the electroplating method, the sputtering method is used to form the transition metal layer, which is beneficial to better cover some small defects on the raw foil (such as pinholes and small holes) and improve the tensile strength and quality of the raw foil.

[0029] In some embodiments, according to the first aspect, a tenth example of the first aspect is provided, after peeling and before removing the release film, further comprising:

[0030] forming a transition metal layer on the surface of the raw foil to obtain a composite structure, which sequentially includes the transition metal layer, the raw foil and the release film;

[0031] The composite structure is fixed on both sides of the base film to obtain a sandwich structure, wherein the transition metal layer is close to the base film and the release film is far away from the base film.

[0032] A composite foil can be obtained by this technical solution, wherein the raw foil and the transition metal layer constitute an alloy layer, and a base film is arranged between the two alloy layers, which can improve the overall tensile strength of the alloy layer.

[0033] In some embodiments, according to the first aspect, an eleventh example of the first aspect is provided, after peeling and before removing the release film, further comprising:

[0034] forming a transition metal layer on the surface of the raw foil;

[0035] adhering a release film to the transition metal layer;

[0036] removing the release film on the raw foil to obtain a composite structure, which sequentially includes the raw foil, the transition metal layer and the release film;

[0037] The composite structure is fixed on both sides of the base film to obtain a sandwich structure, in which the raw foil is close to the base film and the release film is far away from the base film.

[0038] This technical solution can be used to obtain a composite foil of another structure, in which the raw foil and the transition metal layer constitute an alloy layer, and a base film is arranged between the two alloy layers, which can improve the overall tensile strength of the alloy layer (including the raw foil and the transition metal layer).

[0039] In some embodiments, according to the first aspect, a twelfth example of the first aspect is provided, wherein the fixing includes adhering with an adhesive.

[0040] The composite structure is adhered to both sides of the base film using an adhesive, which is simple to operate and saves costs.

[0041] In some embodiments, according to the first aspect, a thirteenth example of the first aspect is proposed, after obtaining the sandwich structure and before removing the release film, the method further includes: semi-curing the sandwich structure. After removing the release film, the method further includes: curing.

[0042] Semi-curing and curing are beneficial to combine the base film and the composite structure more firmly together and improve the overall stability and tensile strength of the composite foil.

[0043] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0045] Figure 1-Figure 4 Schematic diagram of the structure obtained by each step of preparing a composite foil according to an embodiment of the present application.

[0046] Figure 5-Figure 10 This is a schematic diagram of the structure obtained by each step of preparing a composite foil according to another embodiment of the present application.

[0047] Description of reference numerals:

[0048] 100 is copper foil, 200 is release film, 300 is transition metal layer, 400 is base film, and 500 is adhesive layer. DETAILED DESCRIPTION

[0049] The exemplary embodiments of the present disclosure will be described in more detail below with reference to the accompanying drawings. Although the exemplary embodiments of the present disclosure are shown in the accompanying drawings, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0050] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application. The terms "including" and "having" and any variations thereof in the specification and claims of this application and the above-mentioned figure descriptions are intended to cover non-exclusive inclusions.

[0051] For simplicity, only some numerical ranges are explicitly disclosed herein. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, although not explicitly stated, each point or single value between the range endpoints is included in the range. Thus, each point or single value can be combined with any other point or single value as its own lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range.

[0052] In the description of this article, it should be noted that, unless otherwise specified, "above" and "below" are inclusive of the number itself, and the "multiple" in "one or more" means more than two (including two).

[0053] The above-mentioned summary of the invention of the present application is not intended to describe each disclosed embodiment or each implementation in the present application. The following description more specifically illustrates exemplary embodiments. In many places throughout the application, guidance is provided by a series of examples, which can be used in various combinations. In each example, enumeration is only used as a representative group and should not be interpreted as exhaustive.

[0054] In secondary batteries, the current collector is the collection carrier for electron energy transfer. Copper foil is usually used as the negative electrode current collector. As the performance requirements of secondary batteries increase, the thickness of copper foil is getting thinner and thinner. However, when copper foil is prepared by electrolysis, it is difficult to peel off the cathode roller if the copper foil is too thin, and it is easy to tear the edge, which makes it difficult to prepare thinner copper foil.

[0055] The main reason for the tearing of the copper foil is that when the copper foil is peeled off from the surface of the cathode roller, the bonding force between the copper foil and the end of the cathode roller is too large. On the one hand, since the cathode roller is powered on and immersed in the electrolyte, an electrolytic copper layer will inevitably be deposited on the end of the cathode roller, making it difficult to peel off the copper foil at the end of the cathode roller. On the other hand, if the end of the cathode roller is not polished well, the right-angle damage of the end of the cathode roller is caused, and the end surface grinding finish is low, it will also cause the bonding force between the cathode roller and the copper foil at the end of the roller to be too large. In order to solve the problem of copper layer deposition at the end of the cathode roller, it is generally adopted to seal the end of the cathode roller to prevent the electrolyte from contacting the end of the cathode roller to reduce copper deposition. However, it is not easy to achieve complete sealing of the end of the cathode roller.

[0056] Therefore, how to improve the edge tearing problem of copper foil has become an important research topic.

[0057] In order to solve the above problems, the present application provides a new method for preparing foil, wherein a release film is adhered to the raw foil of a roll body, and the raw foil and the release film are peeled off from the roll body together. The release film can improve the stability of the raw foil, so that when the raw foil is peeled off from the roll body, the tearing problem of the raw foil can be effectively improved.

[0058] Specifically, the first aspect of the present application provides a method for preparing a foil, comprising the following steps:

[0059] The green foil is formed on the roll body by electrolysis;

[0060] Adhering a release film to the raw foil;

[0061] Peeling the raw foil and the release film off the roller;

[0062] Remove the release film.

[0063] In this application, "release film" refers to an adhesive film that can be removed after being treated under certain conditions. The peel strength between the release film and the raw foil can change with the change of conditions. The peel strength of the release film will change when at least one of the following conditions changes: light energy, light wavelength, and light exposure time.

[0064] The present application can improve the stability of the raw foil by adhering a release film to the raw foil, so that when the raw foil is peeled off from the roller, the tearing problem of the raw foil can be effectively improved. The release film can be removed from the raw foil later without affecting the performance of the raw foil. The method can realize the preparation of thinner raw foil, especially ultra-thin raw foil, and compared with the existing preparation method, the width of the raw foil can be increased, thereby improving the quality and use effect of the raw foil.

[0065] In some embodiments, before removing the release film, the peel strength between the release film and the raw foil may be 1 N / 25 mm or more, preferably 1-5 N / 25 mm. During the process of removing the release film, the peel strength between the release film and the raw foil may be 0.3 N / 25 mm or less.

[0066] The present application optimizes the peel strength of the release film within the above range, so that the raw foil and the release film can be peeled off from the roller body together, thereby improving the problems of raw foil tearing and tape breakage, and the release film can be removed from the surface of the raw foil after peeling, thereby reducing the release film residue.

[0067] In the case where the release film is a UV anti-adhesion film, when the peeling strength between the release film and the raw foil is too high before removing the release film, high light energy is required to reduce the peeling strength, otherwise the release film cannot be completely removed from the raw foil. However, the ultra-thin copper foil limits the light energy to not be too high, which leads to the problem that the release film cannot be completely removed from the raw foil under insufficient light energy. If the peeling strength between the release film and the raw foil is too low before removing the release film, the edge tearing problem still exists in the process of peeling the raw foil from the cathode roller.

[0068] In some specific embodiments, before removing the release film, the peel strength between the release film and the green foil may be 1N / 25mm, 1.5N / 25mm, 2N / 25mm, 2.5N / 25mm, 3N / 25mm, 3.5N / 25mm, 4N / 25mm, 4.5N / 25mm or 5N / 25mm.

[0069] In some specific embodiments, during the process of removing the release film, the peel strength between the release film and the raw foil may be 0.3 N / 25 mm, 0.2 N / 25 mm, 0.1 N / 25 mm, or 0 N / 25 mm.

[0070] In some embodiments, the release film includes a UV anti-viscosity film, which is a special adhesive tape that has strong viscosity under normal conditions and whose viscosity decreases sharply after being irradiated with UV light.

[0071] By optimizing the type of release film, it is convenient and quick to remove it after the peeling step, which can reduce damage to the raw foil.

[0072] In some specific embodiments, the thickness of the release film may be 1-10 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm. Before removing the release film, the peel strength between the release film and the raw foil increases with the thickness of the release film.

[0073] In some embodiments, removing the release film includes: changing at least one of the following conditions: light energy, light wavelength, and illumination time, so that the peeling strength between the release film and the raw foil is reduced to less than 0.3N / 25mm, thereby removing the release film.

[0074] The release film of the present application is easy to remove, has a simple process, is convenient to operate, and is suitable for large-scale industrial production.

[0075] In some specific embodiments, the release film is removed by changing the conditions to reduce the peel strength between the release film and the raw foil to 0.3 N / 25 mm, 0.2 N / 25 mm, 0.1 N / 25 mm or 0 N / 25 mm.

[0076] In some specific embodiments, when the release film is a UV anti-viscosity film, it can be removed by ultraviolet (UV) irradiation. The energy and time of UV irradiation are not particularly limited in the present application, as long as the UV anti-viscosity film can be removed.

[0077] In some embodiments, the release film covers the entire surface of the green foil.

[0078] Adhering the release film to the entire surface of the raw foil (the surface facing away from the roll body) is conducive to completely peeling off the raw foil, improving the problems of edge tearing and tape breakage, and can obtain a copper foil with a roll length of more than 10,000 meters without the risk of tape tearing and tape breakage in the middle. In the case where the release film covers part of the surface of the raw foil, the uncovered part of the raw foil may also have a tearing problem when peeling off, which in turn leads to edge tearing and tape breakage problems. Therefore, the present application preferably makes the release film cover the entire surface of the raw foil.

[0079] In some embodiments, the raw foil is a copper foil. Forming the raw foil on the roller body includes: forming a copper foil raw foil on the roller body using an electrolyte. The electrolyte may include: 70-90 g / L of copper ions, 90-120 g / L of sulfuric acid, 20-50 mg / L of chloride ions, 3-20 mg / L of brightener, 30-200 mg / L of inhibitor, and 30-200 mg / L of leveler. The brightener includes one or more of sodium polydisulfide propane sulfonate (SPS), sodium 3-mercaptopropane sulfonate (MPS), and sodium N,N-dimethyldithiocarbonyl propane sulfonate (DPS). The inhibitor includes one or more of polyethylene glycol (PEG) and hydroxyethyl cellulose (HEC). The leveler includes one or more of low molecular weight collagen (e.g., collagen 3000), gelatin, and nitrogen-containing heterocyclic quaternary ammonium salts.

[0080] The electrolyte formula is related to the properties of the resulting copper foil. The present application optimizes the electrolyte formula to reduce holes on the copper foil, enhance its mechanical properties, improve its tensile strength, improve edge tearing and broken problems, and improve the quality of the copper foil.

[0081] In some embodiments, the green foil may have a thickness of 1-2 μm.

[0082] The thinner the raw foil is, the more likely it is to have edge tearing and tape breakage problems. However, the method of the present application can be used to prepare ultra-thin raw foil with a thickness of 1-2 μm, which is not prone to edge tearing and tape breakage problems, thus overcoming the difficulty in preparing ultra-thin raw foil.

[0083] In some specific embodiments, the green foil may have a thickness of 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, or 2 μm.

[0084] In some embodiments, after the peeling and before the release film is removed, the method further includes: forming a transition metal layer on the surface of the raw foil.

[0085] By forming a transition metal layer on the surface of the raw foil, an alloy foil can be obtained, which can not only improve the strength of the raw foil, such as tensile strength, thereby improving the mechanical properties of the copper raw foil; it can also cover some small defects on the raw foil (such as pinholes and small holes) to improve the quality of the raw foil; it can also increase the thickness and corrosion resistance of the raw foil.

[0086] In some embodiments, the material of the transition metal layer may include one or more of nickel and molybdenum.

[0087] By optimizing the material of the transition metal layer, it is beneficial to improve the strength of the raw foil (such as tensile strength) and obtain high-quality raw foil.

[0088] In some specific embodiments, the raw foil may be a copper foil, and the transition metal layer may include nickel. The resulting copper-nickel alloy foil has high tensile strength and strong corrosion resistance.

[0089] In some embodiments, the transition metal layer may have a thickness of 20-100 nm.

[0090] Controlling the thickness of the transition metal layer within the above range is beneficial to enhancing the mechanical properties of the alloy.

[0091] In some specific embodiments, the thickness of the transition metal layer may be 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm or 100nm. As the thickness of the transition metal layer increases, the tensile strength of the alloy foil increases accordingly. However, when the thickness of the transition metal layer is too large, the effect of improving the tensile strength of the raw foil is no longer obvious, but the production cost increases. Therefore, the thickness of the transition metal layer is controlled within the range of 20-100nm in this application.

[0092] In some embodiments, the transition metal layer is formed by sputtering. Optionally, the sputtering method includes one or more of magnetron sputtering, direct current sputtering, and radio frequency sputtering.

[0093] Compared with the electroplating method, the sputtering method is used to form the transition metal layer, which is beneficial to better cover some small defects (such as pinholes and small holes) on the raw foil, obtain a uniform transition metal layer, and improve the tensile strength and quality of the raw foil.

[0094] In some embodiments, after peeling and before removing the release film, the method further includes:

[0095] forming a transition metal layer on the surface of the raw foil to obtain a composite structure, which sequentially includes the transition metal layer, the raw foil and the release film;

[0096] The composite structure is fixed on both sides of the base film to obtain a sandwich structure, wherein the transition metal layer is close to the base film and the release film is far away from the base film.

[0097] The technical solution can be used to obtain a composite foil, in which the raw foil and the transition metal layer form an alloy layer, and a base film is arranged between the two alloy layers, which can improve the overall tensile strength of the alloy layer. Specifically, the composite copper foil includes a raw foil, a transition metal layer, a base film, a transition metal layer and a raw foil stacked from top to bottom.

[0098] In some embodiments, after peeling and before removing the release film, the method further includes:

[0099] forming a transition metal layer on the surface of the raw foil;

[0100] adhering a release film to the transition metal layer;

[0101] removing the release film on the raw foil to obtain a composite structure, which sequentially includes the raw foil, the transition metal layer and the release film;

[0102] The composite structure is fixed on both sides of the base film to obtain a sandwich structure, in which the raw foil is close to the base film and the release film is far away from the base film.

[0103] The technical solution can be used to obtain another structure of composite foil, in which the raw foil and the transition metal layer form an alloy layer, and a base film is arranged between the two alloy layers, which can improve the overall tensile strength of the alloy layer (including the raw foil and the transition metal layer). Specifically, the composite copper foil includes a transition metal layer, a raw foil, a base film, a raw foil and a transition metal layer stacked from top to bottom.

[0104] In some embodiments, the fixing includes bonding with an adhesive. By applying an adhesive on both surfaces of the base film, the composite structure can be firmly fixed to both sides of the base film, so that the base film and the composite structure are better combined, the overall tensile strength is improved, the operation is simple, and the cost is saved.

[0105] In some specific embodiments, the adhesive may include one or more of epoxy resin and maleic anhydride-modified polyolefin (eg, maleic anhydride-modified polypropylene).

[0106] In some embodiments, after obtaining the sandwich structure and before removing the release film, the method further includes: semi-curing the sandwich structure. After removing the release film, the method further includes: curing. Semi-curing includes: keeping warm at 70-90° C. in nitrogen or inert gas. Curing includes: keeping warm at 70-90° C. in nitrogen or inert gas.

[0107] Semi-curing and curing are beneficial to combine the base film and the composite structure more firmly together and improve the overall stability and tensile strength of the composite foil.

[0108] In some embodiments, the material of the base film may include one or more of polyethylene terephthalate, polypropylene, etc.

[0109] In some embodiments, the base film may have a thickness of 2-6 μm, such as 2 μm, 2.5 μm, 2.9 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm or 6 μm. A thin base film can reduce the overall thickness of the composite foil.

[0110] The present application is further described below in conjunction with the examples. The following examples describe the disclosure of the present application in more detail, and these examples are merely illustrative, because it is obvious to those skilled in the art that various modifications and variations are made within the scope of the disclosure of the present application. Unless otherwise stated, all reagents used in the examples are commercially available or synthesized according to conventional methods, and the instruments used in the examples are commercially available.

[0111] Preparation of copper foil

[0112] Example 1

[0113] (1) Preparation of electrolyte

[0114] The electrolyte composition is: copper ion 70-90g / L, sulfuric acid 90-120g / L, chloride ion 20-50mg / L, brightener 3-20mg / L, inhibitor 30-200mg / L, leveler 30-200mg / L. The brightener is sodium polydisulfide dipropane sulfonate (SPS), the inhibitor is polyethylene glycol (PEG), and the leveler is gelatin.

[0115] (2) Preparation of electrolytic copper foil

[0116] Electrolytic copper foil with a thickness of 1.5 μm was prepared by adjusting the current and the speed of the cathode roller. The diameter of the cathode roller was 2.7 m, the speed was 8 m / min, and the current was 5700 A.

[0117] (3) Adhesion UV anti-viscosity film

[0118] Prepare a coating UV viscosity-reducing liquid with a solid content of 20wt%: weigh the UV viscosity-reducing composition (powder material, purchased from China Lucky Group Co., Ltd.) with a weighing instrument, add ethyl acetate solvent, and stir for 20 minutes to obtain a coating UV viscosity-reducing liquid with a solid content of 20wt%. After standing and degassing for 10 minutes, apply it on the PET substrate with a coater. Dry in an arched oven at 80°C to completely evaporate the solvent, leaving a flat viscosity-reducing film with a width equal to the width of the cathode roller and a thickness of 2μm. At this point, the UV viscosity-reducing film is completed. After that, under the action of the lamination roller, the UV viscosity-reducing film is adhered to the rough surface of the raw foil.

[0119] Before peeling, test the peel strength between the UV anti-viscosity film and the electrolytic copper foil. The test method includes the following steps:

[0120] ① After adhering the UV anti-sticking film to the rough surface of the raw foil, cut a section of sample from the cathode roller (the sample includes the raw foil and the UV anti-sticking film adhered to the raw foil), and use a sampling slicer to cut it into strips with a length and width of 25mm×100mm respectively.

[0121] ② Use 3M double-sided tape to stick the sample on the glass plate, and use a 2Kg push roller to roll it back and forth three times.

[0122] ③ Use 3M transparent tape to peel off the sample 10mm in length and then use the high-speed rail tensile machine to test the peeling strength. The test adopts the 90-degree peeling method. Basic parameters of the high-speed rail tensile machine: clamp spacing 100mm, speed 50mm / min.

[0123] (4) Peeling

[0124] The copper foil is peeled off from the cathode roll together with the release film.

[0125] (5) Removal of UV anti-viscosity film

[0126] After UV light irradiation, the UV anti-viscosity film is removed to obtain copper foil. After UV light irradiation, the peel strength between the UV anti-viscosity film and the electrolytic copper foil is measured. The peel strength is the peel strength between the UV anti-viscosity film and the raw foil during the process of removing the UV anti-viscosity film. The test method of peel strength is as follows:

[0127] ① After ultraviolet light irradiation, a section of sample (the sample includes the raw foil and the UV anti-sticking film adhered to the raw foil) is cut from the cathode roller and sliced ​​into samples with a length and width of 25 mm × 100 mm using a sampling slicer.

[0128] ② Use 3M double-sided tape to stick the sample on the glass plate, and use a 2Kg push roller to roll it back and forth three times.

[0129] ③ Use 3M transparent tape to peel off the sample 10mm in length and then use the high-speed rail tensile machine to test the peeling strength. The test adopts the 90-degree peeling method. Basic parameters of the high-speed rail tensile machine: clamp spacing 100mm, speed 50mm / min.

[0130] Embodiment 2-5

[0131] The method described in Example 1 was followed, except that before peeling, the peel strength between the UV anti-viscosity film and the electrolytic copper foil was different from that in Example 1, and the peel strength between the release film and the raw foil increased with the increase of the thickness of the release film, as shown in Table 1 below.

[0132] Table 1

[0133]

[0134] Embodiment 6-8

[0135] The method described in Example 1 was followed, except that during the ultraviolet light irradiation, the peel strength between the UV anti-viscosity film and the electrolytic copper foil was different from that in Example 1, as shown in Table 2 below.

[0136] Table 2

[0137]

[0138] Examples 9-11

[0139] The method described in Example 1 was followed, except that an electrolytic copper foil having a thickness different from that of Example 1 was prepared by adjusting the current and the cathode roller linear speed, as shown in Table 3 below.

[0140] The thickness of copper foil is positively correlated with the current and negatively correlated with the cathode roller speed. Thickness calculation formula:

[0141] Copper foil thickness (μm) = copper electrochemical equivalent × current × electroplating efficiency ÷ cathode roller speed ÷ copper density ÷ cathode roller width ÷ 60. The copper electrochemical equivalent is 1.186g / AH, the electroplating efficiency is 98%, and the copper density is 8.95g / cm 3 , cathode roller width 1.02m. The thickness of the copper foil is controlled by adjusting the current and the cathode roller linear speed. For example: the preparation parameters of 1μm thick copper foil: current 4500A, cathode roller linear speed 9.5m / min. The preparation parameters of 1.5μm thick copper foil: current 4500A, cathode roller linear speed 6.3m / min.

[0142] Table 3

[0143] serial number Copper foil thickness / μm Example 1 1.5 Example 9 1 Example 10 2 Embodiment 11 0.8

[0144] Comparative Example 1

[0145] The method described in Example 1 was followed, except that no UV anti-adhesion film was adhered and the copper foil was directly peeled off from the cathode roller.

[0146] Tear area test of raw foil

[0147] Tear edge area test:

[0148] The tearing edge is mainly concentrated on the edge of the cathode roller, and the cathode roller is exposed in the tearing edge. The tearing edge area percentage = tearing edge width / / cathode roller width × 100%. The tearing edge width = cathode roller width - copper foil width, where the copper foil width is the width value of the smallest width of the copper foil on the cathode roller, that is, the width value of the narrowest part of the copper foil on the cathode roller. The results are shown in Table 4 below.

[0149] Table 4

[0150] serial number Torn edge area Release film residue Example 1 0.1% none Example 2 0.8% none Example 3 0.2% none Example 4 10% none Example 5 0.4% part Example 6 0.5% none Example 7 0.65% none Example 8 0.7% part Example 9 1% none Example 10 0.08% none Embodiment 11 9.2% none Comparative Example 1 50% /

[0151] It can be seen from the above embodiments and comparative examples that the present application can improve the stability of the electrolytic copper foil by adhering a release film on the electrolytic copper foil, so that when the electrolytic copper foil is peeled off from the cathode roller, the tearing problem of the electrolytic copper foil can be effectively improved and the tearing area can be reduced.

[0152] Preparation of alloy foil

[0153] Example 12

[0154] (1) Preparation of electrolyte

[0155] Same as Example 1.

[0156] (2) Preparation of electrolytic copper foil

[0157] Same as Example 1.

[0158] (3) Adhesion UV anti-viscosity film

[0159] Same as Example 1.

[0160] (4) Peeling

[0161] Same as Example 1.

[0162] (5) Formation of nickel layer

[0163] A nickel layer is formed on the surface of the electrolytic copper foil by magnetron sputtering, and the thickness of the nickel layer is 20 nm.

[0164] (6) Removal of UV anti-viscosity film

[0165] The UV anti-viscosity film is irradiated with 30% UV light with an energy of 600mJ / cm 2 , remove the UV anti-viscosity film and obtain the copper-nickel alloy foil.

[0166] Embodiment 13

[0167] The method described in Example 12 is followed, except that the type of transition metal layer is different from that in Example 12, as shown in Table 5 below.

[0168] Table 5

[0169] serial number Transition metal layer Example 12 Nickel layer Embodiment 13 Molybdenum layer

[0170] Examples 14-17

[0171] The method described in Example 12 is followed, except that the thickness of the transition metal layer is different from that in Example 12, as shown in Table 6 below.

[0172] Table 6

[0173] serial number Thickness of transition metal layer / nm Example 12 20 Embodiment 14 50 Embodiment 15 100 Example 16 10 Embodiment 17 150

[0174] Embodiment 18

[0175] The method described in Example 12 is followed, except that the method for forming the nickel layer is different from that in Example 12, as shown in Table 7 below.

[0176] Table 7

[0177] serial number Method for forming nickel layer Example 12 Magnetron sputtering Embodiment 18 Acid Nickel Plating

[0178] Alloy foil strength test

[0179] Tensile strength test:

[0180] The sample was punched into a sample with a width of 15 mm and a length of 150 mm, and a tensile test was performed using a high-speed rail tensile machine at room temperature and pressure (25°C, 0.1 MPa). The initial length was set to 50 mm, and the tensile test was performed at a tensile rate of 5 mm / min until the sample broke and the tensile test was stopped. The maximum tensile force F borne by the sample when it was broken was recorded, and the tensile strength of the organic support layer was calculated according to T=F / S. Where S is the initial cross-sectional area of ​​the sample, which is equal to the product of the width of the sample and the thickness of the sample. The test results are shown in Table 8 below.

[0181] Table 8

[0182] serial number Tensile strength / Mpa Metal layer thickness / nm Example 12 150 20(Nickel layer) Embodiment 13 138 20(Molybdenum layer) Embodiment 14 172 50(Nickel layer) Embodiment 15 175 100(Nickel layer) Example 16 130 10(Nickel layer) Embodiment 17 176 150(Nickel layer) Embodiment 18 121 20(electroplated nickel layer)

[0183] It can be seen from the above embodiments that a high-strength alloy foil can be obtained by adopting the method of the present application.

[0184] Preparation of composite copper foil

[0185] Embodiment 19

[0186] (1) Preparation of electrolyte

[0187] Same as Example 12.

[0188] (2) Preparation of electrolytic copper foil

[0189] Same as Example 12.

[0190] (3) Adhesion UV anti-viscosity film

[0191] Same as Example 12.

[0192] (4) Peeling

[0193] Same as Example 12. The obtained structure is as follows Figure 1 As shown, it includes an electrolytic copper foil 100 and a release film 200 (ie, a UV anti-adhesion film).

[0194] (5) Formation of nickel layer

[0195] Same as Example 12. Figure 2 The composite structure shown includes an electrolytic copper foil 100 , a release film 200 (ie, a UV anti-adhesion film) and a transition metal layer 300 (ie, a nickel layer).

[0196] (6) Preparation of sandwich structure

[0197] Epoxy resin adhesive was uniformly coated on both surfaces of a 2.9 μm thick polypropylene PP base film 400 to form an adhesive layer 500. The composite structure obtained in step (5) was adhered to both surfaces of the PP base film to obtain a composite structure as shown in FIG. Figure 3 The sandwich structure shown, where the nickel layer is close to the base film.

[0198] (7) Semi-ripening

[0199] Set the temperature of the oven filled with nitrogen or inert gas to 80°C and bake for 24 hours.

[0200] (8) Removal of UV anti-viscosity film

[0201] The UV anti-viscosity film is irradiated with 30% UV light with an energy of 600mJ / cm 2 , remove the UV anti-viscosity film and obtain Figure 4 The composite copper foil shown.

[0202] (9) Ripening

[0203] Set the temperature of an oven filled with nitrogen or inert gas to 80°C and bake and keep warm for 72 hours to allow the adhesive to solidify and the molecular chains to solidify completely.

[0204] Embodiment 20

[0205] (1) Preparation of electrolyte

[0206] Same as Example 12.

[0207] (2) Preparation of electrolytic copper foil

[0208] Same as Example 12.

[0209] (3) Adhesion UV anti-viscosity film

[0210] Same as Example 12.

[0211] (4) Peeling

[0212] Same as Example 12. The obtained structure is as follows Figure 5 As shown, it includes an electrolytic copper foil 100 and a release film 200 (ie, a UV anti-adhesion film).

[0213] (5) Formation of nickel layer

[0214] Same as Example 12. Figure 6 The structure shown includes an electrolytic copper foil 100 , a release film 200 (ie, a UV anti-adhesion film) and a transition metal layer 300 (ie, a nickel layer).

[0215] (6) Preparation of sandwich structure

[0216] A UV anti-adhesion film is adhered to the nickel layer to obtain Figure 7 The UV anti-viscosity film on the electrolytic copper foil is then irradiated with 30% UV light with an energy of 600 mJ / cm 2 , thereby removing the UV anti-viscosity film on the electrolytic copper foil, and obtaining Figure 8 The composite structure shown in FIG. Epoxy resin adhesive is uniformly coated on both surfaces of a polypropylene PP base film 400 having a thickness of 2.9 nm to form an adhesive layer 500. The composite structure is adhered to both surfaces of the PET base film to obtain a composite structure as shown in FIG. Fig. 9 The sandwich structure shown.

[0217] (7) Semi-ripening

[0218] Set the temperature of the oven filled with nitrogen or inert gas to 80°C and bake for 24 hours.

[0219] (8) Removal of UV anti-viscosity film

[0220] The UV anti-viscosity film is irradiated with 30% UV light with an energy of 600mJ / cm 2 , remove the UV anti-viscosity film and obtain Fig.10 The composite copper foil shown.

[0221] (9) Ripening

[0222] Set the temperature of an oven filled with nitrogen or inert gas to 80°C and bake and keep warm for 72 hours to allow the adhesive to cross-link and cure, and the molecular chains to cure completely.

[0223] Embodiment 21

[0224] The method described in Example 19 was followed, except that no half-ripening and aging were performed.

[0225] Strength test of composite copper foil

[0226] Tensile strength test:

[0227] The sample was punched into a sample with a width of 15 mm and a length of 150 mm, and a tensile test was performed using a high-speed rail tensile machine at room temperature and pressure (25°C, 0.1 MPa). The initial length was set to 50 mm, and the tensile test was performed at a tensile rate of 5 mm / min until the sample broke and the tensile test was stopped. The maximum tensile force F borne by the sample when it was broken was recorded, and the tensile strength of the organic support layer was calculated according to T=F / S. Where S is the initial cross-sectional area of ​​the sample, which is equal to the product of the width of the sample and the thickness of the sample. The test results are shown in Table 9 below.

[0228] Table 9

[0229] serial number Tensile strength / Mpa Embodiment 19 230 Embodiment 20 220 Embodiment 21 210

[0230] It can be seen from the above embodiments and comparative examples that a high-strength composite copper foil can be obtained by adopting the method of the present application.

[0231] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope of the claims.

Claims

1. A method for preparing a foil, characterized in that: The following steps are involved: The green foil is formed on the roll body by electrolysis; adhering a release film to the raw foil; peeling the raw foil and the release film off the roller body; The release film is removed.

2. The method according to claim 1, characterized in that Before removing the release film, the peel strength between the release film and the raw foil is 1N / 25mm or more, preferably 1-5N / 25mm; During the process of removing the release film, the peeling strength between the release film and the raw foil is less than 0.3 N / 25 mm.

3. The method according to claim 2, characterized in that The release film includes a UV anti-adhesion film.

4. The method according to any one of claims 1 to 3, characterized in that Removing the release film includes: changing at least one of the following conditions: light energy, light wavelength, and light exposure time, so that the peeling strength between the release film and the raw foil is reduced to less than 0.3N / 25mm, thereby removing the release film.

5. The method according to any one of claims 1 to 4, characterized in that The release film covers the entire surface of the raw foil.

6. The method according to any one of claims 1 to 5, characterized in that The green foil has a thickness of 1-2 μm.

7. The method according to any one of claims 1 to 6, characterized in that After the peeling and before the release film is removed, the method further includes: forming a transition metal layer on the surface of the raw foil.

8. The method according to claim 7, characterized in that The material of the transition metal layer includes one or more of nickel and molybdenum.

9. The method according to claim 7 or 8, characterized in that: The thickness of the transition metal layer is 20-100 nm.

10. The method according to any one of claims 7 to 9, characterized in that: The transition metal layer is formed by sputtering; optionally, the sputtering method includes one or more of magnetron sputtering, direct current sputtering, and radio frequency sputtering.

11. The method according to any one of claims 1 to 6, characterized in that: After peeling and before removing the release film, the method further comprises: forming a transition metal layer on the surface of the raw foil to obtain a composite structure, which sequentially comprises the transition metal layer, the raw foil and the release film; The composite structure is fixed on both sides of the base film to obtain a sandwich structure, wherein the transition metal layer is close to the base film and the release film is far away from the base film.

12. The method according to any one of claims 1 to 6, characterized in that After peeling and before removing the release film, the method further comprises: forming a transition metal layer on the surface of the raw foil; Adhering the release film on the transition metal layer; removing the release film on the raw foil to obtain a composite structure, which sequentially comprises the raw foil, the transition metal layer and the release film; The composite structure is fixed on both sides of the base film to obtain a sandwich structure, wherein the raw foil is close to the base film and the release film is far away from the base film.

13. The method according to claim 11 or 12, characterized in that: The fixing includes adhering with an adhesive.

14. The method according to claim 11 or 12, characterized in that: After obtaining the sandwich structure and before removing the release film, the method further includes: semi-cooking the sandwich structure; After removing the release film, the method further includes: performing aging.

Citation Information

Cited By

  • Secondary battery and preparation method thereof, energy storage system and electric equipment

    CN120149569A

  • Additive of 1-micron electrolytic copper foil and preparation method of 1-micron electrolytic copper foil

    CN121915467A

  • Additive for 1-micron electrolytic copper foil and method for producing 1-micron electrolytic copper foil

    CN121915467B